PREVALENCE OF VOLUNTARY MEDICAL MALE CIRCUMCISION AMONG MEN ATTENDING NAKIVALE HC III ISINGIRO. A CROSS-SECTIONAL STUDY. - ANDREW, NATWIJUKA; Muhumuza, Felix; Otwine, Anne Tweheyo (Student’s Journal of Health Research Africa, 2024)
Background: Medical male circumcision is the surgical removal of the foreskin which covers the penis of a male human being. The study aims to determine the Prevalence of voluntary medical male circumcision. Methodology: A cross-sectional study employing quantitative measures. The study involved adult males who attend healthcare services at Nakivale Health Center III in the age bracket of 15 to 50 years. The data was exported to the IBM statistical package for Social Sciences (SPSS) version 20 software for analysis. Data was analyzed using percentages and frequencies for univariate and Chi-square for bivariate analysis. Results: The majority of the participants had received VMMC (65.2%) and received it from the health facility (68.8%). On age, the majority of subjects were aged between 18 to 39 years 106(76.8%) and the least were aged 40-49 years 14(10.1%), on marital status, most of the participants were single 68(49.3%) and the least were divorced 3(2.2%). The majority of the participants had attained a primary level of education (42.2%) and the least had tertiary education 13(9.4%). On occupation, most of the participants were students 39(28.3%) and the least were unemployed 16(11.6%), on religious affiliation most of the participants were protestant 50(36.2%) and the least were Muslims 10(7.2%). Conclusion: The majority of the respondents had received VMC from facilities most of whom were below 39 years preferably due to continued sensitization of communities. Recommendations: Independent stakeholders need to improve on sensitizing the society about VMMC through linking with nursing institutions to help in making up camps and outreaches and community education in these remote areas.